2017
DOI: 10.22456/1982-8918.72972
|View full text |Cite
|
Sign up to set email alerts
|

A Prática Corporal Como Expressão Da Imaginação Da Criança Na Brincadeira: Uma Perspectiva Da Psicologia Histórico-Cultural

Abstract: Resumo: Pretendeu-se, com este estudo, estabelecer relações entre a brincadeira e os processos de aprendizagem e de desenvolvimento da criança à luz da psicologia histórico-cultural, elucidando como a brincadeira de faz de conta se materializa como prática corporal construtora de significados e de sentidos. Para tanto, o texto está organizado em três momentos: o primeiro apresenta a abordagem histórico-cultural e algumas informações sobre o principal autor que a constituiu; o segundo trata de definir os fundam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 1 publication
0
5
0
1
Order By: Relevance
“…Many other games were also related to the colors, especially in the High-Contrast and Luminous cubes. When playing with imagination, the child uses concepts and generalizations that are beyond the possibilities of reality but can be articulated in their actions in fantasy 8 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Many other games were also related to the colors, especially in the High-Contrast and Luminous cubes. When playing with imagination, the child uses concepts and generalizations that are beyond the possibilities of reality but can be articulated in their actions in fantasy 8 .…”
Section: Discussionmentioning
confidence: 99%
“…The tactile cube encouraged touching actions and games such as sliding the hand and shaking, swinging, turning, spinning, and knocking were mentioned. Sampaio et al 8 demonstrated that children between the ages of 4 and 5 years use speech as an intermediate assistant while planning their actions 8 . The child uses speech to assist in processing their thoughts while solving a task and, at the same time, interposes in the process of developing their thinking.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…El niño podrá conocer su cuerpo y sus posibilidades, aumentando posteriormente su autoestima. Reconocerá las fortalezas que tiene, intentará afrontar retos con su propio dominio corporal y favoreciendo, poco a poco, una mayor autoconfianza, llegando a obtener la necesaria autonomía para su día a día (Martinek, Holland & Seo, 2019;Martínez-Martínez & González-Hernández, 2018;Missana, Rajhans, Atkinson & Grossmann, 2014;Sampaio, De David, Filho & Húngaro, 2017).…”
Section: Sobre Los Contenidos a Enseñarunclassified